Analysis of The Implementation of Internal Control Systems That Influence the Quality of The Government Financial Statements - R. , Ait Novatiani; R. , Wedi Rusmawan Kusumah (International Journal of Psychosocial Rehabilitation, 2020)
Government financial statements are one of the tools of accountability in the administration of government; for that, the government financial statements must reflect the transparency and accountability of government financial management so as to show quality government financial statements. This study aims to analyze the application of internal control systems, the quality of government financial statements, and the effect of the application of internal control systems on the quality of government financial statements. The population in this study is the regional apparatus organization (OPD) in West Bandung Regency, which consists of offices and agencies. Based on the results of the study, it was concluded that the implementation of internal control systems in regional apparatus organizations (OPD) in West Bandung Regency is adequate, the financial statements of regional apparatus organizations (OPD) in West Bandung Regency are quality, and the application of internal control systems has an influence on the quality of government financial statements.